European glacial dust deposits: Geochemical constraints on atmospheric dust cycle modeling. Issue 21 (12th November 2014) - Rousseau, Denis‐Didier; Chauvel, Catherine; Sima, Adriana; Hatté, Christine; Lagroix, France; Antoine, Pierre; Balkanski, Yves; Fuchs, Markus; Mellett, Claire; Kageyama, Masa; Ramstein, Gilles; Lang, Andreas
Abstract For a long time global paleodust numerical simulations have greatly underestimated dust sources other than modern deserts. Recent modeling experiments incorporating glaciogenic sources of dust have positively improved the agreement between model and paleodust data. This highlights the importance of accurately representing all areas potentially subjected to deflation during an investigated interval. Geochemical results, obtained from European loess sequences collected along a 50°N transect, combined with dust emission simulations reveal the geographical distribution of the most important European dust sources between 34 ka and 18 ka. We demonstrate that most European dust traveled only a few hundred kilometers or less within the boundary layer from its source before deposition. We conclude that our results encourage acquisition of similar geochemical data for other relevant areas in the world. Further, they could provide critical constraints to benchmark atmospheric models, contributing to improve their performance in simulating dust cycle and associated climate feedbacks.